Photoluminescent BaMoO4 nanopowders prepared by complex polymerization method (CPM) - Marques, APD; de Melo, DMA; Paskocimas, C. A.; Pizani, P. S.; Joya, M. R.; Leite, E. R.; Longo, Elson [UNESP] (Elsevier B.V., 2006)
The BaMoO4 nanopowders were prepared by the Complex Polymerization Method (CPM). The structure properties of the BaMoO4 powders were characterized by FTIR transmittance spectra, X-ray diffraction (XRD), Raman spectra, photoluminescence spectra (PL) and high-resolution scanning electron microscopy (HR-SEM). The XRD, FTIR and Raman data showed that BaMoO4 at 300 degrees C was disordered. At 400 degrees C and higher temperature, BaMoO4 crystalline scheelite-type phases could be identified, without the presence of additional phases, according to the XRD, FTIR and Raman data. The calculated average crystallite sizes, calculated by XRD, around 40 nm, showed the tendency to increase with the temperature. The crystallite sizes, obtained by HR-SEM, were around of 40-50 nm. The sample that presented the highest intensity of the red emission band was the one heat treated at 400 degrees C for 2 h, and the sample that displayed the 'highest intensity of the green emission band was the one heat treated at 700 degrees C for 2 h. The CPM was shown to be a low cost route for the production of BaMoO4 nanopowders, with the advantages of lower temperature, smaller time and reduced cost. The optical properties observed for BaMoO4 nanopowders suggested that this material is a highly promising candidate for photoluminescent applications. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: BaMoO4; nanopowders; complex polymerization method; photoluminescence; amorphous